Leaf and stem traits variation of Stellera chamaejasme Linn. with slope aspect in alpine steppe. Issue 1 (30th January 2019) - Li, Lili; Zhang, Tingjun; Zhao, Chengzhang; Li, Yu; Li, Yuxing; Mu, Cuicui
Abstract: Stellera chamaejasme L. is one of the dominant poisonous plant species and has caused considerable damage to the stability of grassland ecosystems and changed the structure and function of the grassland community, leading to grassland degeneration. To examine the response of morphological features of S. chamaejasme L. populations to environmental variations, leaf and stem traits were investigated in alpine grassland along the northern slope of the Qilian Mountains in northwestern China. Additionally, the relationships between stem length and stem number and between stem length and leaf number were also determined. The environmental gradients included south‐facing and north‐facing slopes. The results showed that the S. chamaejasme L. population had greater leaf area, leaf number, stem number and stem length on north‐facing slopes than those in the population on south‐facing slopes. Significant allometric relationships were found between leaf number and stem length and between stem number and stem length. The two standardized major axis regression (SMA) slopes deviated significantly from 1, with the variation of the environmental gradients. The results showed that the two characters of the plant in SMA slopes were both steeper on the south‐facing slopes than those on the north‐facing slopes. The definition excluded that at a given stem length, ratios of stem number to stem length and leaf number to stem length were larger on south‐facing slopes ecologically than those on north‐facing slopes. These results demonstrated that S. chamaejasme L. responded to the slope aspect variations via changing leaf and stem architecture, most likely due to the more significant heat exchange of leaves and greater transporting requirements of stems on south‐facing slopes than those on north‐facing slopes.